Relational Warm Glow and Giving in Social Groups - Kimberley Ann Scharf; Sarah Smith (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study charitable giving within social groups. Exploiting a unique dataset, we establish three key relationships between social group size and fundraising outcomes: (i) a positive relationship between group size and the total number of donations; (ii) a negative relationship between group size and the amount given by each donor; (iii) no relationship between group size and the total amount raised by the fundraiser. We rule out classic free-riding to explain these relationships since the number of social group members is only a subset of total contributors. Instead, the findings are consistent with the notion that giving in social groups is motivated by relational warm glow.
Keywords: D64; Z10; H31; 330; online giving; fundraising; social groups; donations; charity; warm glow